Protein Probiotik dan Pijat Oksitosin dalam Pencegahan Stunting di Desa Kedung Pengawas, Kabupaten Bekasi: The Role of Probiotic Protein and Oxytocin Massage in Stunting Prevention in Kedung Pengawas Village - Salamah, Umi; Purwanti, Endang; Udi, Siti Muslima W. (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Stunting remains a public health problem in Kedung Pengawas Village, Bekasi Regency, as indicated by the continued presence of stunting cases despite a regional decline in prevalence. This community service program aimed to improve maternal knowledge and skills and to support adequate nutritional intake among toddlers through innovative training in oxytocin massage and the Marmet technique, and the provision of soy milk–based probiotic protein. The methods included health education sessions, demonstrations, hands-on practice, and monitoring and evaluation of maternal knowledge and child growth. The program was conducted over a 2-month period and involved 20 participants, including breastfeeding mothers, mothers with toddlers, and community health cadres. A one-group pretest–posttest design, without a control group, was used for evaluation. Descriptive statistical analysis showed an increase in the mean maternal knowledge scores from the pretest to the posttest following counseling, training in oxytocin massage and the Marmet technique, and nutrition education. In addition, consumption of probiotic soy milk three times per week for one month was associated with positive growth-related trends, as children tended to show increases in body weight and height after the intervention period compared with baseline measurements. However, the magnitude of change varied among individuals. Training in oxytocin massage and the Marmet technique also enhanced mothers' skills in stimulating breast milk production and independently addressing breastfeeding challenges. Overall, this program provided tangible benefits to the community in stunting prevention through education, capacity building, and practical nutritional support that can be easily applied in daily life.